Social media use, uncertainty, and negative affect in times of pandemic crisis - Yun Wu; Zihao An; Yi Lin; Jingyue Zhang; Bo Jing; Kaiping Peng (Digital Health, 2023)
Objective A common assertion in the social media literature is that passive media use undermines affective wellbeing, and active media use enhances it. The present study investigated the effects of social media use on negative affective wellbeing during pandemic crises and examined the mechanism underlying these effects through perceived uncertainty. Methods Three studies were conducted during the Delta variant phase in the post-peak period of the COVID-19 pandemic in China. Participants were recruited from the medium-high-risk infection areas in late August 2021. Study 1 used a cross-sectional survey to explore the relationships between social media use, uncertainty, and negative affect during the pandemic crisis. Study 2 employed a repeated-measures experiment to demonstrate how social media use and (un)certainty impact negative affect. Study 3 utilized a one-week experience sampling design to examine the role of uncertainty in the relationship between social media use and negative affect in real life. Results Despite some inconsistencies regarding social media use's direct effect on negative affect, across the three studies, perceived uncertainty was critical in linking pandemic-related social media use to individuals’ negative affect, particularly for passive use. Conclusions The relationships between social media use and affective wellbeing are complex and dynamic. While the perception of uncertainty provided an underlying mechanism that links social media use to individuals’ affective wellbeing, this mechanism may be further moderated by individual-level factors. More research is needed as we seek to understand how social media use impacts affective wellbeing in uncertain contexts.